A Novel Strategy for Cervical Cancer Prevention Using Cervical-Vaginal Self-Collected Samples Shows High Acceptability in Women Living in Low-Income Conditions from Bucaramanga, Colombia - Torrad-García LM; Martínez-Vega RA; Rincon-Orozco B (Dove Medical Press, 2020)
Laura M Torrado-García, Ruth A Martínez-Vega, Bladimiro Rincon-Orozco Microbiology School, Universidad Industrial De Santander, Bucaramanga, Santander, ColombiaCorrespondence: Bladimiro Rincon-Orozco Email blrincon@uis.edu.coIntroduction: Human papillomavirus molecular detection prevents cervical cancer (CC). To widen its use, cervical-vaginal self-collection devices are proposed. Our aim was to determine the acceptability of self-sampled cervical-vaginal protocol and the reproducibility of results using HPV detection brushes in a low-income Colombian population between 35 and 65 years old.Methods: Cross-sectional study including women classified as medium to high-risk for developing CC by using a short-standardized survey. After receiving instructions, women self-collected a cervical-vaginal sample. Subsequently, a perception survey was conducted.Results: Four hundred and twenty-three women performed self-collected sampling. The median age was 46.5 years (IQR 40– 52), 56.5% were housewives, and 55.1% had finished elementary school. About 99% of the population (n=419) considered that they understood the instructions, 19.4% (n=82) reported having concerns about the self-collected sample, 9.2% (n=39) distrusted the results because of the self-collection, 7.3% (n=31) felt uncomfortable with the procedure, and 9.7% (n=41) reported some pain. The majority would recommend the procedure to others (99%), 88.5% of the sampled population preferred the self-collected method, 4% preferred conventional cytology, and 7.3% were not sure. The reasons behind favoring the self-collected procedure included privacy (n= 149, 40.1%), comfort (n=110, 29.7%), easiness (n=52, 14%), reliability (n=46, 12.4%), and less painful (n=110, 29.7%). The percentage of HPV detection agreement between the self-collected and the healthcare professional-collected procedures was 98.99% (Cohen’s Kappa=0.9774).Conclusion: Women living in low-income households in Bucaramanga, Colombia preferred the self-sampling procedure because it was easy to use, convenient, and private, resulting in 98% acceptability, and positioning it as an excellent tool for CC prevention.Keywords: cervical smear, uterine cervical neoplasms, female, self-collected HPV